A Bibliometric Analysis of Character and Moral Education Research on Gifted Children - Gügen, Rabia Hümeyra; Çap, Aleyna; Kırca, Beyza; Kırca, Beyza (SHS Web of Conferences, 2024)
Gifted individuals possess superior potential in intelligence, creativity, and wisdom. However, to maximize this potential for themselves and society, they must develop in the cognitive, affective, and socio emotional domains, supported by character education. Current research in giftedness emphasizes the need for a paradigm shift to support gifted individuals' character development and ethical sensitivity within the education system. This study aims to carry out a bibliometric analysis of studies on character and moral education in gifted education and to examine the field from a panoramic perspective through parameters such as trends, prominent authors, institutions, and countries. This analysis aims to identify current needs, provide a panoramic summary of studies conducted in this area, and guide future research.